Insecticide-Treated Nets Utilization and Associated Factors Among Pregnant Women in Miesso Woreda, Eastern Ethiopia: Observational Study - Tesfaye T; Mengistie B; Egata G; Bekele H; BT Merga; Eshetu B; Balis B (Dove Medical Press, 2022)
Tigist Tesfaye,1 Bezatu Mengistie Alemu,2 Gudina Egata,2 Habtamu Bekele,3 Bedasa Taye Merga,2 Bajrond Eshetu,3 Bikila Balis3 1Department of Public Health, Oromia Regional Health Bureau, Addis Ababa, Ethiopia; 2School of Public Health, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Midwifery, School of Nursing and Midwifery, College of Health and Medical Science, Haramaya University, Harar, EthiopiaCorrespondence: Bikila Balis, School of Nursing, College of Health and Medical Science, Haramaya University, P.O. Box: 235, Harar, Ethiopia, Tel +251921788619, Email bik.balis2008@gmail.comBackground: Even though most sub-Saharan Africa adopted the World Health organization guidelines for malaria prevention, the coverage of insecticide-treated nets by pregnant women is low, where 28 million pregnant women did not receive insecticide-treated nets services. Likewise, only 13- 51.4% of pregnant women utilize insecticide-treated nets in Ethiopia.Methods: A community-based cross-sectional study was conducted in Miesso woreda from April 01 to 30, 2017, among 424 pregnant women. A multi-stage cluster sampling technique was used to select the study participants. A structured interviewer-based administered questionnaire and observational checklist were used to collect the data. The collected data were entered into Epi data version 3.1 and exported to SPSS version 23 for analysis. Multiple logistic regression models were fitted to identify factors associated with insecticide-treated nets utilization. Adjusted odds ratios along 95% CI were estimated to measure the strength of the association and declared statistical significance at a p-value < 0.05.Results: Of a total respondents, 39.9% (95% CI: 34.9- 44.2%) utilize insecticide-treated nets. Pregnant women from rural (AOR = 2.05, 95% CI: 1.14, 3.38), employed women (AOR = 1.80, 95% CI: 1.13, 2.86), monthly income > 1050 Ethiopian total birr (AOR = 2.02, 95% CI: 1.06, 3.84), third trimester pregnancy (AOR = 2.19, 95% CI: 1.09, 4.40), and having antenatal care for current pregnancy (AOR = 3.86, 95% CI: 1.63, 9.10) were factors significantly associated with insecticide-treated nets.Conclusion: The utilization of insecticide-treated nets is relatively low. Residence, occupational status, monthly income, stage of pregnancy, and antenatal care status were factors significantly associated with insecticide-treated net utilization among pregnant women.Keywords: insecticide-treated nets, malaria, pregnant women, Miesso woreda, Ethiopia